Pediatric Lunotriquetral Dissociation and Static Volar Intercalated Segmental Instability After Radial Neck Fracture - Lauren E. Tagliero, MD; William J. Shaughnessy, MD; Alexander Y. Shin, MD (Journal of Hand Surgery Global Online)
Pediatric patients can pose challenges with regard to both diagnosis and obtaining an accurate history and physical examination, as well as in treatment strategies, as options become limited when physes remain open. This case report examines a 12-year-old boy who sustained a radial neck fracture after a ground-level fall. Although his elbow injury was treated appropriately, he developed wrist pain that progressed to static volar intercalated segmental instability deformity in the context of a carpal instability nondissociative wrist. A paucity of cases of pediatric patients with open physes and static volar intercalated segmental instability deformity exists. Adult treatment typically consists of some form of arthrodesis; however, this should be approached with caution in young patients. This case highlights the importance of careful wrist examination in all elbow injuries, as well as the challenges in surgical treatment options for pediatric patients.